2022
DOI: 10.3390/healthcare10122357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Cognitive-Behavioral Therapy Intervention on the Rowers of the Junior Spain National Team

Abstract: Cognitive-behavioral therapy has been implemented in the training plans of many athletes and sports teams, obtaining very good results for the improvement of mental skills. These effects are achieved through improvements in cognitive skills such as motivation, mental concentration, and self-confidence, all within an appropriate context of specific physical, technical, and tactical training. However, there are few studies that consider the analysis of performance from a psychological point of view from a gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This can be considered as a sub-phase for subsequent jumps over 40 centimeters, where no significant differences were found (p > .05). One possible response to help athletes 12 Efectos del entrenamiento cluster sobre la hipertrofia muscular: Una revisión sistemática Miguel Alarcón-Rivera, Luis Benavides-Roca, Cristian Salazar Orellana, Eduardo Guzmán-Muñoz Gender Differences in Physical Performance and Psychological Assessment Among Cuban National Athletics Team Feria-Madueño, Adrián, Montoya, César, López, Larien y González-Carballido, Luis Gustavo 12 find strategies that satisfy their psychological needs of self-efficacy may be addressed by Isorna-Folgar et al (2022), who recently found an effective cognitive intervention program for rowers from the Spanish national junior team.…”
Section: Discussionmentioning
confidence: 99%
“…This can be considered as a sub-phase for subsequent jumps over 40 centimeters, where no significant differences were found (p > .05). One possible response to help athletes 12 Efectos del entrenamiento cluster sobre la hipertrofia muscular: Una revisión sistemática Miguel Alarcón-Rivera, Luis Benavides-Roca, Cristian Salazar Orellana, Eduardo Guzmán-Muñoz Gender Differences in Physical Performance and Psychological Assessment Among Cuban National Athletics Team Feria-Madueño, Adrián, Montoya, César, López, Larien y González-Carballido, Luis Gustavo 12 find strategies that satisfy their psychological needs of self-efficacy may be addressed by Isorna-Folgar et al (2022), who recently found an effective cognitive intervention program for rowers from the Spanish national junior team.…”
Section: Discussionmentioning
confidence: 99%
“…The coordination of communication between coaches, medical and psychological staff at all stages of training and competition is particularly important in the athlete preparation process [ 94 , 95 ]. The individualization of psychological intervention is significant as well [ 96 ]. The practical effect of the research is the possibility to identify the directions of personalized treatment of athletes in the process of training and their psychological preparation for competitions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, psychological interventions are beneficial in enhancing both psychological well-being and athletic performance [ 234 ]. These effects are achieved through improvements in cognitive skills, such as motivation, mental concentration, and self-confidence [ 235 , 236 ].…”
Section: Performance Enhancement and Mental Strategiesmentioning
confidence: 99%
“…Cognitive behavioral therapy (CBT) has been effectively implemented in training programs for athletes and sports teams, yielding significant results in enhancing mental skills. These improvements are attained through a comprehensive training approach, encompassing physical, technical, and tactical training [ 236 ]. The relevance of psychological interventions in sports is increasingly recognized for their role in enhancing psychological well-being and optimizing athletic performance.…”
Section: Performance Enhancement and Mental Strategiesmentioning
confidence: 99%
See 1 more Smart Citation